Characterization of the novel genotype avian hepatitis E viruses from outbreaks of hepatic rupture haemorrhage syndrome in different geographical regions of China. Issue 6 (25th August 2018) - Su, Qi; Li, Yang; Zhang, Yawen; Zhang, Zhihui; Meng, Fanfeng; Cui, Zhizhong; Chang, Shuang; Zhao, Peng
Abstract: Since 2016, hepatic rupture haemorrhage syndrome (HRHS) has emerged in layer and broiler breeder hens in several provinces of China, and novel genotype avian hepatitis E viruses were detected from these chickens. To gain a better understanding of the genetic properties of the novel avian HEV strain, the capsid gene of four isolates from birds at four farms experiencing HRHS in different geographical regions were determined and compared with those of reported pathogenic and nonpathogenic avian HEV isolates as well as mammalian HEVs. Results showed that all those isolates share 80.1%–88.2% nucleotide sequence identity and 89.3%–91.9% amino acid sequence identity with other published avian HEV strains, while phylogenetic analysis further demonstrate that a novel genotype avian HEV was epidemic in China. Meanwhile, sequence analysis revealed that those novel isolates contain various amino acid mutations and even a hypervariable region in their major antigenic domains, which might be the critical factors for the pathogenicity elevation and even change their antigenicity. The data presented in this report will enhance the current understanding of the epidemiology and genetic diversity of the novel genotype avian HEV in China and provide additional insight into the critical factors that determine the pathogenicity of it.